Data Clustering: Algorithms and Applications - Aggarwal, Charu C.; Reddy, Chandan K. (Chapman & Hall/CRC data mining and knowledge discovery series, 2014)
In this book, top researchers from around the world cover the entire area of clustering, from basic methods to more refined and complex data clustering approaches. They pay special attention to recent issues in graphs, social networks, and other domains. The book explores the characteristics of clustering problems in a variety of application areas. It also explains how to glean detailed insight from the clustering process--including how to verify the quality of the underlying clusters--through supervision, human intervention, or the automated generation of alternative clusters.